Simulation, design and synthesis of polybenzoxazine with different main‐chain structures and properties: A comparative study. Issue 19 (6th March 2023) - Li, Xin Kang; Shen, Jun Wei; Lin, Hai Lan; Zhang, Zhao Xin; Zhang, Xun Tao; Bian, Jun; Chen, Dai Qiang
Abstract: In order to explore effective strategies to fabricate main‐chain polybenzoxazine (PBZ) thermosetting resin for structural material applications, here, five PBZ with different molecular structures, that is, poly(Co‐ddm), poly(Co‐BPA‐ddm‐Co)main, poly(Ph‐BPA‐ddm‐Co)main, poly(Ph‐BPA‐ddm‐Ph)main and poly(Ph‐ddm) were designed, synthesized and compared by introducing unsaturated fatty chains through the Mannich reaction with cardanol. The structure and properties of five PBZ with different structure were systematically investigated by using Fourier transform infrared (FTIR), NMR, water absorption and mechanical tests. FTIR and NMR tests indicated that five PBZ with different molecular structures were successfully synthesized. The mechanical tests indicated that the impact strength of the double‐capped cardanol‐based main‐chain PBZ was 243% higher than that of the traditional PBZ. The water absorption of main‐chain PBZ was higher than that of diamine PBZ, and the water absorption of poly(Ph‐BPA‐ddm‐Co)main was the lowest in the main‐chain PBZ. Based on the experimental results, five PBZ amorphous cells with different structures were successfully established. It indicated that the main chain PBZ showed better thermomechanical properties than the traditional diamine PBZ due to high crosslinking conversion and hydrogen bond density. Moreover, the modulus and glass transition temperature of the main chain structure containing unsaturated fatty chains did not decrease significantly. Abstract :